Esports Fan Engagement: A Comparison of PC and Console Esports Team Fans - Huettermann, Marcel; Pizzo, Anthony D. (Frontiers in Sports and Active Living, 2022)
Esports, competitive video game competitions, are a leading digital innovation at the nexus of sports, business, and technology. Given their prominent position, esports have received extensive media and academic attention. In particular, esports fans, primarily tech-savvy and affluent young adults, have been the foci of this attention. Accordingly, a large number of studies has centered on these influential consumers, examining their motives to spectate, support, and follow esports teams and players. To date, esports have been examined very broadly, neglecting differences in the multitude of games, genres, and platforms which influence their consumption. In particular, the platform (or medium), plays a substantial role in how consumers engage with esports teams and players. These platforms include personal computers (PCs) and video gaming consoles. The purpose of this study is to identify differences in how fans of PC and console based esports teams engage with their favorite esports team. We collected data from both PC and console esports team fans via an online survey (N = 514), analyzing said data using structural equation modeling and multigroup analysis. Our results highlight that fans of console-based esports teams value both emotional engagement and management cooperation, underscoring the more intimate and personal experience afforded by consoles (vis-à-vis PCs). Overall, our study elucidates differences in esports fan engagement and helps to further identify critical differences that influence esports consumer behavior.